2016
DOI: 10.1111/jnc.13881
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers as a measure of disease activity and treatment efficacy in relapsing‐remitting multiple sclerosis

Abstract: Cerebrospinal fluid (CSF) biomarkers can reflect different aspects of the pathophysiology of relapsing-remitting multiple sclerosis (RRMS). Understanding the impact of different disease modifying therapies on the CSF biomarker profile may increase their implementation in clinical practice and their appropriateness for monitoring treatment efficacy. This study investigated the influence of first-line (interferon beta) and second-line (natalizumab) therapies on seven CSF biomarkers in RRMS and their correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
128
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 38 publications
17
128
1
1
Order By: Relevance
“…In CIS/RRMS patients, the decrease in sNfL levels correlated inversely with longer time since start of DMTs independent of recent relapses. Notably, treatment effects on CSF NfL levels have already been shown for fingolimod, natalizumab, and rituximab in MS patients 13, 14, 15, 16, 17, 47. Although this study was not primarily designed to investigate treatment effects, our results suggest that DMTs reduce sNfL levels, supporting their value for monitoring treatment response.…”
Section: Discussionsupporting
confidence: 68%
“…In CIS/RRMS patients, the decrease in sNfL levels correlated inversely with longer time since start of DMTs independent of recent relapses. Notably, treatment effects on CSF NfL levels have already been shown for fingolimod, natalizumab, and rituximab in MS patients 13, 14, 15, 16, 17, 47. Although this study was not primarily designed to investigate treatment effects, our results suggest that DMTs reduce sNfL levels, supporting their value for monitoring treatment response.…”
Section: Discussionsupporting
confidence: 68%
“…11,52 Only 1 previous study considered CHIT1 in the context of prognosis in MS but was limited in terms of a smaller study population and of sampling patients with an indication to switch therapies at different time points in disease instead of newly diagnosed patients. 53 Baseline (diagnostic stage) CSF CHI3L1 levels have been associated with earlier progression to disability. 50,51 There is a similar trend in our study, but we demonstrated this to be secondary to the substantially stronger association with CHIT1.…”
Section: Discussionmentioning
confidence: 99%
“…(http://guidetopharmacology.org/GRAC/ ObjectDisplayForward?objectId = 59 (accessed 19 September 2019)) CCL2 levels in CNS are reduced during increased disease activity in MS [82]. According to the discovery of Franciotta D et al, CCL2 can be constitutively produced in the brain and CCL2 CSF levels in acute MS are lower than those in stable MS [34].…”
Section: Ccl2/ccr2mentioning
confidence: 99%
“…Thus, CXCL13 may be involved in recruiting mononuclear cells expressing CXCR5 or CXCR3 to the intrathecal compartment in MS [105]. CXCL13 levels are reduced by natalizumab treatment in MS [53,82]. According to Quinn JL et al, the antibody against CXCL13 could block Tfh transport and significantly reduce disease expression in Th17 EAE (EAE that induced by the myelin-specific Th17 cells transfer in C57BL / 6 J mice) [91].…”
Section: Cxcl13/cxcr5mentioning
confidence: 99%